Penambahan Serabut Kelapa pada Tanah Terhadap Uji Kompaksi - Ratmanyanty, Widya (Paulus Civil Engineering Journal, 2025)
Good soil quality is essential to ensure the strength and stability of structures built on it. This study aims to determine the soil's physical characteristics and the effect of adding coconut coir using compaction tests. The study is divided into two stages, namely: 1) testing the soil's physical properties; 2) performing compaction tests. According to the AASHTO classification, the soil is classified as A-7-6, meaning it is a clay soil; based on the USCS classification, the soil falls into the category of inorganic clay with low to medium plasticity. The effect of adding coconut fiber to the soil samples—up to 2% addition—resulted in an increase in optimum moisture content of 14.8% for point 1 and 14.1% for point 2. An increase was also observed in the dry unit weight with up to 2% addition: 6.3% for point 1 and 8.5% for point 2.